2016
DOI: 10.1142/s0219581x16600127
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mesoporous Titania–Silica Monolith Composites — A Comprehensive Study on their Photocatalytic Degradation of Acid Blue 113 Dye Under UV Light

Abstract: The present work deals with the synthesis of bi-continuous macro and mesoporous crack-free titania–silica monoliths, with well-defined structural dimensions and high surface area. The work also highlights their potential photocatalytic environmental applications. The highly ordered titania–silica monoliths are synthesized through direct surface template method using organic precursors of silica and titania in the presence of surface directing agents such as pluronic P123 and PEG, under acetic acid medium. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The techniques, methods and procedures reported in literature for the remediation of AB113 dye can be broadly classified into biological-cum-chemical [13,20,21,28,51] electrocoagulation [39], physical methods using UV radiations [36,44,[46][47][48], photocatalytic degradation [66,74], low frequency ultrasound assisted degradation [40], nanomaterials [49] and use of inorganic materials including activated carbons [16,34,42,43,45,63]. Nevertheless, huge initial cost in installing operational plant, high-operational cost, regeneration problem, secondary pollutants, sensitivity to variations in wastewater input, interference by some wastewater constituents, and residual sludge generation are some associated problems in these methods [11,61].…”
Section: Introductionmentioning
confidence: 99%
“…The techniques, methods and procedures reported in literature for the remediation of AB113 dye can be broadly classified into biological-cum-chemical [13,20,21,28,51] electrocoagulation [39], physical methods using UV radiations [36,44,[46][47][48], photocatalytic degradation [66,74], low frequency ultrasound assisted degradation [40], nanomaterials [49] and use of inorganic materials including activated carbons [16,34,42,43,45,63]. Nevertheless, huge initial cost in installing operational plant, high-operational cost, regeneration problem, secondary pollutants, sensitivity to variations in wastewater input, interference by some wastewater constituents, and residual sludge generation are some associated problems in these methods [11,61].…”
Section: Introductionmentioning
confidence: 99%
“…Little information about its discoloration, degradation and adsorption from textile industrial effluent (TIE) has been reported. Various techniques, methods, and procedures have been reported in the literature, which are listed as electrocoagulation 1 , photocatalytic degradation 2 , 3 , biological–chemical procedures 4 – 13 , ultrasound methods with low frequency 14 , sono catalytic procedures 15 , 16 , and nanomaterials 17 , 18 . Various inorganic and nanomaterials are reported, of which activated carbon is widely used in textile industries 5 , 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first example of photoactive SiO 2 /TiO 2 monoliths offering heterogeneous photoinduced air treatment at the gas–solid interface. Indeed if the preparation of TiO 2 /SiO 2 monoliths has been well described, then their photoactivity has been studied only in solution by the study of dye decoloration. , The second very important advantage is indeed “geometric”. As working now within the volume of the photocatalysts and not only on their outer surface while providing upgraded photoefficiency (Figure , Table ), the photocatalytic systems could be miniaturized, offering the potential toward indoor air treatment within vehicles/homes while drastically limiting the associated encumbrance or footprint penalty.…”
Section: Resultsmentioning
confidence: 99%